E-Readiness Operator Pelaksana dalam Penerapan Aplikasi Administrasi Kependudukan Cepat Akurat Terintegrasi (PANDU CAKTI) Di Kabupaten Tulungagung - Kautsar Azmi Saddad, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Population and Civil Registration Office of Tulungagung Regency launched a new solution in the form of an online application called the Integrated Fast Accurate Population Administration Service (Pandu Cakti). With the Pandu Cakti online application, the Tulungagung community no longer needs to come to the Dispendukcapil Office to take care of population documents at their respective village or kelurahan offices. With the intention to simplify and speed up the process of managing population administration. Therefore, this study aims to measure the level of e-readiness ability of operators implementing the integrated fast accurate population administration application (PANDU CAKTI) in Tulungagung Regency. the type of research used is quantitative research. While the approach used in this research is a quantitative descriptive approach with data collection techniques with questionnaire surveys, documentation, observation, and interviews. The results showed that indicators of perceived Ease of Use, attitude Toward of Using, behavioral Intention to Use, and actual System Usage were in the ready category in the application of panducakti innovation. However, the perceived usefulness indicator falls into the category of quite ready.